MICROHABITAT BREADTH OF FISH COMMUNITY ALONG THE VAMANAPURAM RIVER, SOUTH KERALA - Kingston, S. David; Arun, L. K.; Natarajan, P. (Journal of Indian Fisheries Association, 2006)
The microhabitat breadth of Vamanapuram River fish community was studied in detail. The microhabitat variables selected were relative depth, focal point velocity, water column depth, mean water velocity and substrate. Puntius filamentosus had the highest breadth in three dimensions in both stream and river habitats showing a generalistic mode of resource utilization. Garra mullya, Labeo dero and Glossogobius giurb; are specialists in the usage of microhabitat variables in the stream habitat while these are G. mullya, Etroplus maculatus and Aplocheilus lineatus in river habitat. Danio aequipinnatus showed extreme variations along focal point velocity variable in both habitats indicating an. opportunistic behaviour. Keywords: Vaman.apuram River, fish community, microhabitat breadth, focal point velocity